The Dynamics of U.S. China Security Rivalry in the South China Sea through a Neo-Realist Approach - Muthia Sakti (Pt. Anagata Sembagi Education, 2025)
This study investigates the dynamics of U.S.–China security rivalry in the South China Sea through a neo-realist perspective using a systematic literature review of recent scholarly work. The findings show that strategic competition between Washington and Beijing is driven primarily by structural pressures of the international system rather than ideological disputes or policy miscalculations. China’s naval modernization, A2/AD capabilities, and island militarization reflect long-term hegemonic aspirations to dominate the regional maritime order, while the United States maintains its Indo-Pacific military posture and expands alliance networks to preserve maritime primacy. International institutions and diplomatic mechanisms have failed to mitigate tensions because both powers prioritize national interests above legal norms and cooperative regimes. The rivalry has widened military coalitions, weakened ASEAN strategic autonomy, and entrenched bipolarity across the Indo-Pacific, indicating that conflict escalation is linked to the distribution of power under anarchy rather than contingent diplomacy. This review concludes that without a fundamental shift in structural power, the South China Sea will remain a focal arena of long-term security competition between the United States and China